Humanitarian Intervention and the Jus Cogens Argument: A Critical Observation - Fajri Matahati Muhammadin (Faculty of Law, Universitas Padjadjaran, 2018)
AbstractThe legality of humanitarian intervention has been debated for a long time, both on the level of scholarly works and inter-state politics. Most of the debates surround the sources of international law (international conventions, customary international law, etc.) or functions of the UN or the politics or a combination thereof. However, another level of debate is not usually observed much: the Jus cogens debate. Being a non-derogable norm under international law, the prohibition against the use of force is a classic example of a Jus cogens norm, and humanitarian intervention is argued to breach it. This paper observed and explored the concept of Jus cogens, how is it constructed, and found that humanitarian intervention is not a breach of Jus cogens.Abstrak Legalitas dari intervensi kemanusiaan telah diperdebatkan sejak lama, baik melalui karya ilmiah para ahli maupun dalam politik praktis antar negara. Mayoritas perdebatan berpusat pada sumber-sumber hukum internasional (konvensi internasional, hukum kebiasaan internasional, dan lain-lain), atau fungsi PBB atau perpolitikan atau perpaduan keduanya. Namun, ada satu level perdebatan yang kurang diamati: perdebatan Jus cogens. Sebagai norma yang tidak dapat dikurangi menurut hukum internasional, larangan penggunaan kekerasan bersenjata merupakan contoh klasik norma Jus cogens, dan intervensi kemanusiaan diklaim telah menentangnya. Paper ini mencermati dan mengeksplorasi konsep Jus cogens, bagaimana terbentuknya, dan menemukan bahwa intervensi kemanusiaan bukanlah pelanggaran Jus cogens.DOI: https://doi.org/10.22304/pjih.v5n1.a4